2019
DOI: 10.1002/anie.201903256
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the In Vivo Transport of Anticancer Drugs Using Renal‐Clearable Gold Nanoparticles

Abstract: Precise control of in vivo transport of anticancer drugs in normal and cancerous tissues with engineered nanoparticles is key to the future success of cancer nanomedicines in clinics.T his requires af undamental understanding of how engineered nanoparticles impact the targeting-clearance and permeation-retention paradoxes in the anticancer-drug delivery.Herein, we systematically investigated how renal-clearable gold nanoparticles (AuNPs) affect the permeation, distribution, and retention of the anticancer drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 43 publications
(45 reference statements)
1
55
0
Order By: Relevance
“…Very recently, ultrasmall silica NPs (<10 nm in diameter) were reported by Bradbury and coworkers and were applied as a drug delivery vehicle for inducing ferroptosis and regression of tumor . In addition to silica NPs, the Zheng group has intensively studied renal clearable ultrasmall gold NPs (<2 nm core diameter) to target tumors and deliver the anticancer drug, doxorubicin . Previously, we also reported that an ultrasmall (<5.5 nm) zwitterionic organic nanocarrier, termed Harvard‐Dot or H‐Dot, systemically travels the whole body through the bloodstream without nonspecific tissue uptake, then eventually clears out to the urine exclusively (>80% at 4 h postinjection) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, ultrasmall silica NPs (<10 nm in diameter) were reported by Bradbury and coworkers and were applied as a drug delivery vehicle for inducing ferroptosis and regression of tumor . In addition to silica NPs, the Zheng group has intensively studied renal clearable ultrasmall gold NPs (<2 nm core diameter) to target tumors and deliver the anticancer drug, doxorubicin . Previously, we also reported that an ultrasmall (<5.5 nm) zwitterionic organic nanocarrier, termed Harvard‐Dot or H‐Dot, systemically travels the whole body through the bloodstream without nonspecific tissue uptake, then eventually clears out to the urine exclusively (>80% at 4 h postinjection) .…”
mentioning
confidence: 99%
“…After the distribution phase, renal clearable NPs are rapidly cleared from the major organs through urinary excretion resulting in less background retention in organs and tissues . Due to very low background tissue retention, renal clearable NPs can exhibit a high tumor‐to‐background signal ratio for tumor targeting via the enhanced permeability and retention (EPR) effect, despite the lack of active targeting moieties 9a,c. On the other hand, nonrenal clearable and nonspecific NPs, which are mostly larger in size and/or lipophilic, are retained in the central and peripheral compartments including immune‐related organs such as the liver and spleen 7a,12.…”
mentioning
confidence: 99%
“…[12b] We also used renal clearable AuNPs to deliver awidely used anticancer drug, doxorubicin (DOX), to primary and lung metastatic breast cancers and compared the differences in the tumor targeting and clearance of DOXwith or without being loaded into renal clearable AuNPs. [13] We found that renal clearable AuNPs not only enhanced tumor targeting efficiency and efficacy of DOX but also accelerated clearance of off-target DOX; so that the long-standing targeting-clearance paradox in the anticancer drug delivery was successfully addressed. [13] However,t here are still many fundamental questions regarding differences in the anticancer drug delivery between these renal clearable DDSs and conventional non-renal clearable ones.While renal clearable DDSs are known to be highly permeable to both tumor and normal vasculatures and have much shorter blood retention than conventional nano-DDSs,aquantitative and thorough investigation is highly desired to understand how the high vascular permeability of renal clearable DDSs impacts the intratumoral transport and therapeutic efficacyofanticancer drugs over conventional non-renal clearable ones.…”
mentioning
confidence: 95%
“…[13] We found that renal clearable AuNPs not only enhanced tumor targeting efficiency and efficacy of DOX but also accelerated clearance of off-target DOX; so that the long-standing targeting-clearance paradox in the anticancer drug delivery was successfully addressed. [13] However,t here are still many fundamental questions regarding differences in the anticancer drug delivery between these renal clearable DDSs and conventional non-renal clearable ones.While renal clearable DDSs are known to be highly permeable to both tumor and normal vasculatures and have much shorter blood retention than conventional nano-DDSs,aquantitative and thorough investigation is highly desired to understand how the high vascular permeability of renal clearable DDSs impacts the intratumoral transport and therapeutic efficacyofanticancer drugs over conventional non-renal clearable ones. [14] Herein, we conducted ahead-to-head comparison on the differences in the tumor accumulation, intratumoral transport, and therapeutic index of DOX delivered by 5nmrenal clearable and 30 nm non-renal clearable AuNP-based DDSs, which had comparable tumor targeting efficiency but distinct elimination pathways.Our findings show that renal clearable AuNPs can enhance tumor accumulation, efficacy, and therapeutic index of DOX 2, 7, and 10-fold, respectively, over non-renal clearable AuNPs,e ven though their blood retention is two-fold lower than non-renal clearable ones.…”
mentioning
confidence: 95%
See 1 more Smart Citation